2017
DOI: 10.1515/pjvs-2017-0068
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of some essential oils alone and in combination against the fish pathogen Nocardia seriolae

Abstract: Microplate resazurin assay was applied to investigate the in vitro activity of four essential oils (EOs); cinnamon (Cinnamomum zeylanicum), thyme (Thymus vulgaris), lemongrass (Cymbopogon flexuosus) and tea tree (Melaleuca alternifolia) oils against 80 clinical isolates of the fish pathogen Nocardia seriolae. The checkerboard test was then used to determine the possible synergistic effect of EOs combination against reference type strains of fish nocardiosis. All tested EOs had antibacterial activity against N.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Nocardia seriolae is the causative agent of nocardiosis in cultured fish species [115]. Ismail and Yoshida [116] reported that MIC values of C. Zeylanicum, Thymus vulgaris, Cymbopogon flexuosus, and Melaleuca alternifolia EOs on 80 Nocardia seriolae isolates were in the range of 5 to >5120 µg/mL, and the most effective herb species were C. zeylanicum and T. vulgaris with MICs 5-160 µg/mL, respectively.…”
Section: Nocardia Seriolaementioning
confidence: 99%
“…Nocardia seriolae is the causative agent of nocardiosis in cultured fish species [115]. Ismail and Yoshida [116] reported that MIC values of C. Zeylanicum, Thymus vulgaris, Cymbopogon flexuosus, and Melaleuca alternifolia EOs on 80 Nocardia seriolae isolates were in the range of 5 to >5120 µg/mL, and the most effective herb species were C. zeylanicum and T. vulgaris with MICs 5-160 µg/mL, respectively.…”
Section: Nocardia Seriolaementioning
confidence: 99%
“…Some EOs and some major components of EOs identified in this study have already been reported to possess potent antimicrobial activity, either alone or in combination with other antimicrobials, against different bacteria (Alizadeh Behbahani & Imani Fooladi, 2018; Chouhan et al., 2017; Malik et al., 2019; Tariq et al., 2019; Thielmann et al., 2019), including strains isolated from fish (Ismail & Yoshida, 2017). However, based on interpretative criteria proposed by Aligiannis et al.…”
Section: Discussionmentioning
confidence: 70%
“…These genome databases have revealed new information on N. seriolae epidemiology, pathogenesis, transmission and infection control techniques. Traditionally, the pharmaceutical therapy to overcome fish nocardiosis involves several antibiotics, such as sulfamonomehizol and sulfisizole, which have already been approved in Japan as effective treatments for N. serioale infections (Ismail et al, 2012; Ismail & Yoshida, 2017). However, this effort displayed only partial effectiveness with severe problems of microbial resistance, drug residues and environmental pollution (Ismail & Yoshida, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the pharmaceutical therapy to overcome fish nocardiosis involves several antibiotics, such as sulfamonomehizol and sulfisizole, which have already been approved in Japan as effective treatments for N. serioale infections (Ismail et al, 2012; Ismail & Yoshida, 2017). However, this effort displayed only partial effectiveness with severe problems of microbial resistance, drug residues and environmental pollution (Ismail & Yoshida, 2017). By contrast, vaccination is a more effective strategy to overcome the epidemics of nocardiosis through activating the fish immune system with many advantages in long‐term efficacy protection and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%